Comparison of successful offensive sequences in the group stage of 2018 FIFA World Cup: Eliminated vs. qualified teams - Almeida, C. H. (Science and Medicine in Football, 2019)
This study aimed to compare the offensive sequences that resulted in goals in the group stage of the 2018 FIFA World Cup according to teams` status: eliminated versus qualified for the knockout phase. Successful offensive sequences performed in the group stage by eliminated (n = 39) and qualified teams (n = 83) were notated post-event using an adapted version of the Offensive Sequences Characterisation System, which includes simple and composite performance indicators. Magnitude-based inferences revealed that performances indicators Passes/Duration, Passes/Ball touches, Players/Duration and Passes/Players were key to differentiate eliminated and qualified teams. Performance profiles emerging from qualified teams suggest the ability to impose a faster game pace (of ball passing and collective involvement) is more relevant to offensive effectiveness in elite football than the mere amount of sport-specific actions performed. Although offensive sequences with more passes, ball touches and duration had a possible positive effect on reaching the knockout phase, the offensive behaviours of qualified teams highlighted the importance of `quality possession`. Indeed, offensive sequences involving more players (teamwork) and favouring ball passing instead of individual ball retention seem to facilitate the emergence of goal-scoring events. Considering these findings, professional coaches are encouraged to design playing-form activities aiming to promote team-based offensive strategies, including task constraints to increase the game pace and the frequency of `penetrating passes` into vital playing areas.